Answer:
The measure of angle A is 51 degrees
Answer:
The measure of an angle A=[tex]1^{\circ}[/tex].
Step-by-step explanation:
We are given that an angle [tex]95^{\circ}[/tex] and two sides are 7 in and 9 in in a given figure.
We have to find the value of measurement of angle A.
To find the measurement of angle A we apply sine law.
Sine law:[tex]\frac{a}{sin \alpha}=\frac{b}{sin\beta}=\frac{c}{sin \gamma}[/tex]
Where side a is opposite to angle [tex]\alpha[/tex]
Side b is opposite to angle [tex]\beta[/tex]
Side c is opposite to angle[tex] \gamma[/tex]
We are given an angle 95 degrees and opposite side of given angle is 9 in and the angle A is opposite to side 7 in.
Substituting the values then we get
[tex]\frac{9}{sin 95^{\circ}}=\frac{7}{sin A}[/tex]
[tex]\frac{9}{0.683}=\frac{7}{sin A}[/tex]
[tex] sin A=\frac{7\times 0.683}{9}[/tex]
[tex] sin A=\frac{4.781}{9}=\frac{4781}{9000}[/tex]
[tex] sin A=0.531[/tex]
[tex] A= sin^{-1}(0.531)[/tex]
[tex] A=0.56^{\circ}[/tex]
[tex] A= 1^{\circ}[/tex]
Hence, the measure of an angle A=[tex]1^{\circ}[/tex].
[tex] - 3 + 5i \div - 3 - 4i[/tex]
Answer:
[tex]\frac{-11}{25}+\frac{-27}{25}i[/tex] given you are asked to simplify
[tex]\frac{-3+5i}{-3-4i}[/tex]
Step-by-step explanation:
You have to multiply the numerator and denominator by the denominator's conjugate.
The conjugate of a+bi is a-bi.
When you multiply conjugates, you just have to multiply first and last.
(a+bi)(a-bi)
a^2-abi+abi-b^2i^2
a^2+0 -b^2(-1)
a^2+-b^2(-1)
a^2+b^2
See no need to use the whole foil method; the middle terms cancel.
So we are multiplying top and bottom of your fraction by (-3+4i):
[tex]\frac{-3+5i}{-3-4i} \cdot \frac{-3+4i}{-3+4i}=\frac{(-3+5i)(-3-4i)}{(-3-4i)(-3+4i)}[/tex]
So you will have to use the complete foil method for the numerator. Let's do that:
(-3+5i)(-3+4i)
First: (-3)(-3)=9
Outer:: (-3)(4i)=-12i
Inner: (5i)(-3)=-15i
Last: (5i)(4i)=20i^2=20(-1)=-20
--------------------------------------------Combine like terms:
9-20-12i-15i
Simplify:
-11-27i
Now the bottom (-3-4i)(-3+4i):
F(OI)L (we are skipping OI)
First:-3(-3)=9
Last: -4i(4i)=-16i^2=-16(-1)=16
---------------------------------------------Combine like terms:
9+16=25
So our answer is [tex]\frac{-11-27i}{25}{/tex] unless you want to seprate the fraction too:
[tex]\frac{-11}{25}+\frac{-27}{25}i[/tex]
which two numbers have a mean of 10 and a range of 4
Answer:
12 and 8
Step-by-step explanation:
set two numbers as x and y
mean of 10 → x+y/2=10
range of 4 → x-y=4
x+y=20
+ x-y=4
____________
2x=24, x=12
12-y=4, y=8
Answer:
the answer is 8 and 12 hope it helps
Step-by-step explanation:
Which function described below has the greatest rate of change? I WILL MARK BRAINLIEST
Answer:
C III
Step-by-step explanation:
The rate of change of a linear function is the slope.
f(x) = mx + b is the equation of a linear function whose graph is a straight line. m is the slope.
I f(x) = 4x - 3; m = slope = 4
II f(x) = 1/2 x + 5; m = slope = 1/2
III We can use two points to find the slope.
Let's use points (1, 6) and (2, 12).
m = slope = (y2 - y1)/(x2 x1) = (12 - 6)/(2 - 1) = 6/1 = 6
The three slopes are 4, 1/2, 6.
The greatest rate of change is 6, so the answer is C III.
Events A and B are disjointed.
P(A) = 4/11 ; P(B) = 3/11.
Find P(A or B).
*Answer Options*
7/11
4/11
3/11
8/11
Answer:
7/11
Step-by-step explanation:
Two events are disjoint events if they cannot occur at the same time. It is given that A and B are disjointed events, so A and B cannot occur at the same time i.e. the intersection of two disjoint events will be 0.
For two disjoint events A and B:
P(A or B) = P(A) + P(B)
P(A) is given to be 4/11 and P(B) is given to be 3/11. Using these values in the equation, we get:
P(A or B) = [tex]\frac{4}{11}+\frac{3}{11} = \frac{3+4}{11}=\frac{7}{11}[/tex]
PLEASE!!!! ASAP!!! Two airplanes leave the airport. Plane A departs at a 44° angle from the runway, and plane B departs at a 40° from the runway. Which plane was farther away from the airport when it was 22 miles from the ground? Round the solutions to the nearest hundredth.
Answer:
Plane B was farthest away from the airport
Step-by-step explanation:
This question requires you to visualize the run way as the horizontal distance to be covered, the height from the ground as the height gained by the plane after take of and the distance from the airport as the displacement due to the angle of take off.
In plane A
The take-off angle is 44° and the height gained is 22 ft.
Apply the relationship for sine of an angle;
Sine Ф°= opposite side length÷hypotenuse side length
The opposite side length is the height gained by plane which is 22 ft
The angle is 44° and the distance the plane will be away from the airport after take-off will be represented by the value of hypotenuse
Applying the formula
sin Ф=O/H where O=length of the side opposite to angle 44° and H is the hypotenuse
[tex]Sin44=\frac{O}{H} \\\\\\Sin44=\frac{22}{H} \\\\\\H=\frac{22}{sin44deg} \\\\\\H=31.67[/tex]
31.67 miles
In plane B
Angle of take-off =40°, height of plane=22miles finding the hypotenuse
[tex]sin40deg=\frac{O}{H} \\\\\\sin40deg=\frac{22}{H} \\\\\\H=\frac{22}{sin40deg} \\\\\\H=34.23miles[/tex]
34.23miles
Solution
After take-off and reaching a height of 22 ft from the ground, plane A will be 31.67 miles from the airport
After take-off and reaching a height of 22 ft from the ground, plane B will be 34.23 miles away from the airport.
Answer:
9.33 (flvs)
Step-by-step explanation:
i took the test
16. The dimensions of a window are 3x + 10 and 2x + 6. What is the area of the window?
Answer:
Answer in factored form (3x+10)(2x+6)
Answer in standard form 6x^2+38x+60 ( I bet you they want this answer)
Step-by-step explanation:
The assumption is this is a rectangle.
If you have the dimensions of a rectangle are L and W, then the area is equal to L times W.
So here we just need to multiply (3x+10) and (2x+6).
The answer in factored form is (3x+10)(2x+6).
I bet you they want the answer in standard form.
So let's use foil.
First: 3x(2x)=6x^2
Outer: 3x(6)=18x
Inner: 10(2x)=20x
Last: 10(6)=60
----------------Add up!
6x^2+38x+60
The area of the window is 3x² + 19x + 30
The dimension of the window are 3x + 10 and 2x + 6.
The area of the window can be calculated as follows;
area = lw
Therefore,
area = (3x + 10)(2x + 6)
area = 6x² + 18x + 20x + 60
area = 6x² + 38x + 60
area = 3x² + 19x + 30
read more: https://brainly.com/question/3518080?referrer=searchResults
Use the Counting Principle to find the probability.
rolling a 5 on each of 2 number cubes
Answer:
2/12
Step-by-step explanation:
Rolling a 5 on one die the probability is 1 out of 6 or 1/6 so when you add the second die the probability increases as well as the number of outcomes so you have 1/6+1/6 or 2/12. hope this helps
Answer:
1/36
Step-by-step explanation:
A cube has six sides. On number cubes (also called dice), the sides are numbered 1 through 6. So the probability of rolling a 5 on either cube is 1/6. The probability of rolling a 5 on both cubes is:
P(A and B) = P(A) × P(B)
P(A and B) = 1/6 × 1/6
P(A and B) = 1/36
Rowena walks 3 kilometers a day. How many meters does she walk in three days?
[tex]\huge{\boxed{\text{9,000 meters}}}[/tex]
There are 1,000 meters in each kilometer, so multiply to find the daily number of meters. [tex]3*1000=3000[/tex]
Multiply this by 3 to find the number of meters Rowena walks in three days. [tex]3000*3=\boxed{9000}[/tex]
Find the Inverse of this function f(x)={(3,4),(4,3),(-2,6)}
as you may already know, the inverse of a function has the same exact x,y pairs but backwards, namely f(x)'s domain is f⁻¹(x)'s range.
[tex]\bf \stackrel{f(x)}{\begin{array}{|cc|ll} \cline{1-2} \stackrel{domain}{x}&\stackrel{range}{y}\\ \cline{1-2} 3&4\\ 4&3\\ -2&6\\ \cline{1-2} \end{array}}~\hspace{10em} \stackrel{inverse~of~f(x)}{\begin{array}{|cc|ll} \cline{1-2} \stackrel{domain}{x}&\stackrel{range}{y}\\ \cline{1-2} 4&3\\ 3&4\\ 6&-2\\ \cline{1-2} \end{array}}[/tex]
Write an equation in a point-slope form that passes through the given point with the given slope (3, 5), m = -4 and-1, 8), m = ½
Answer:
[tex]\large\boxed{y-5=-4(x-3)}\\\boxed{y-8=\dfrac{1}{2}(x+1)}[/tex]
Step-by-step explanation:
The point-slope form of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
m - slope
[tex]m=-4,\ (3,\ 5)\\\\y-5=-4(x-3)[/tex]
[tex]m=\dfrac{1}{2},\ (-1,\ 8)\\\\y-8=\dfrac{1}{2}(x-(-1))\\\\y-8=\dfrac{1}{2}(x+1)[/tex]
Solve this inequality: 36 - 7 < 32
You already did. That is a true statement.
32 > 29 [and vice versa]
I am joyous to assist you anytime.
The inequality 29 < 32 is true.
After calculating 36 - 7 which equals 29, we compare this result to 32. The inequality 29 < 32 holds true, so the original inequality 36 - 7 < 32 is correct.
The student has asked to solve the inequality 36 - 7 < 32. To solve this inequality, we need to perform the subtraction on the left side of the inequality first.
When we calculate 36 - 7, we get 29. Now we can compare this result to 32 to determine if the inequality holds true.
Since we are dealing with an inequality, we know that if a value a is less than a value b, then a is indeed smaller in quantity or value compared to b. Here, 29 is indeed less than 32. Therefore, the inequality 29 < 32 is true.
What is the length of the hypotenuse in the right triangle shown below?
Answer:
C. 6√2.
Step-by-step explanation:
Since this is a right angled isosceles triangle bot legs are 6 units long
So h^2 = 6^2 + 6^2 = 72
h = √72 = 6√2.
Answer:
The correct option is C) 6√2.
Step-by-step explanation:
Consider the provided triangle.
The provided triangle is a right angle triangle, in which two angles are 45° and one is 90°.
As both angles are equal there opposite side must be equal.
Thus, the leg of another side must be 6.
Now find the hypotenuse by using Pythagorean theorem:
[tex]a^2+b^2=c^2[/tex]
Substitute a = 6 and b = 6 in [tex]a^2+b^2=c^2[/tex].
[tex](6)^2+(6)^2=(c)^2[/tex]
[tex]36 + 36=(c)^2[/tex]
[tex]72=(c)^2[/tex]
[tex]6\sqrt{2}=c[/tex]
Hence, the length of the hypotenuse in the right triangle is 6√2.
Therefore, the correct option is C) 6√2.
What is 7(x+6)=3(x+9)
Answer:
x= -3.75
Step-by-step explanation:
Answer:
x = -15/4
Step-by-step explanation:
7(x+6)=3(x+9)
Distribute
7x+42 = 3x+27
Subtract 3x from each side
7x-3x+42 = 3x-3x+27
4x +42 = 27
Subtract 42 from each side
4x+42-42 = 27-42
4x =-15
Divide each side by 4
4x/4 =-15/4
x = -15/4
in 135 space shuttle missions, there were two failures. Based on these data, what's the probability of a successful mission?
Answer:
98.518 repeating prercent
Step-by-step explanation:
2 out of 135 can also be written as 2/135
2 divided by 135 is 0.014814814814
that number is the percentage of failures
100% in decimal form is 1.00
1.00 subtracted by the percentage of failures is the percentage of successes
which is .98518518518, 518 repeating move the decimal over 2 and you got the percentage 98.518 repeating
What is the solution to 2x-8 <12?
Answer:
[tex]x < 10[/tex]
Step-by-step explanation:
[tex]2x - 8 < 12 \\ 2x - 8 + 8 < 12 + 8 \\( 2x < 20) \div 2 = x < 10[/tex]
x<10 is the solution to the inequality 2x - 8 < 12
To solve the inequality 2x - 8 < 12, you can follow these steps:
Add 8 to both sides of the inequality:
2x - 8 + 8 < 12 + 8
This simplifies to:
2x < 20
Divide both sides of the inequality by 2:
(2x)/2 < 20/2
This simplifies to:
x < 10
Therefore, the solution to the inequality 2x - 8 < 12 is x < 10.
Learn more about inequalities here:
https://brainly.com/question/30231190
#SPJ6
Two tins are geometrically similar. If the ratio of their volume is 27:64 find the ratio of their curved surface area.
Answer:
9 : 16
Step-by-step explanation:
Given 2 similar figures with linear ratio = a : b, then
area ratio = a² : b² and
volume ratio = a³ : b³
Here the volume ratio = 27 : 64, hence
linear ratio = [tex]\sqrt[3]{27}[/tex] : [tex]\sqrt[3]{64}[/tex] = 3 : 4
Hence area ratio = 3² : 4² = 9 : 16
Which one of the following equations could describe the graph above?
Answer: A. y=(1/2)^x+6
Step-by-step explanation: If this is the graph you’re talking about-
When “a” is less than one, the graph increases exponentially to the left. The smaller the value of a, the steeper the slope of the line.
There is a vertical shift up 6 as well
Which properties of equality are used to solve the following (in no particular order)?
3(x + 12) - 2 = 50
Addition Property of Equality
Subtraction Property of Equality
Division Property of Equality
Combine Like Terms
Distributive Property
All except combine like terms. Since you only have 1 variable.
Hope this helps.
r3t40
Which represents a perfect cube?
8.8.8
8+8+8
9.9.9.9
9+9+9+9+9
Answer:
8.8.8.
Step-by-step explanation:
8.8.8 = 8^3 = 512 Perfect cube.
8+8+8 =24
9.9.9.9 = 6561
9+9+9+9+9 = 45.
None of the others are perfect cubes.
Answer:A 8.8.8
Step-by-step explanation:i did the quiz
The digits of a two-digit number sum to 8. When the digits are reversed, the resulting number is 18 less than the original
number. What is the original number?
Answer:
It's 53.
Step-by-step explanation:
Let the number be xy so the digits are x and y, so:
x + y = 8...........(1)
Reversing the 2 digits we have the number 10y + x and this equals
10x + y - 18 so we have the equation:-
10x + y - 18 = 10y + x
9x - 9y = 18
x - y = 2...........(2) Adding equations (1) and (2) we have:
2x = 10
x = 5
and y = 8 - 5 = 3.
So the original number is 53.
We can check this as follows
Original number is 53 so the reverse is 35 .
53 - 35 = 18 which checks out.
-8(5x+5)+9x(10x+9)=20
[tex]-8(5x+5)+9x(10x+9)=20\\-40x-40+90x^2+81x-20=0\\90x^2+41x-60=0\\\\\Delta=41^2-4\cdot90\cdot(-60)=1681+21600=23281\\\\x=\dfrac{-41\pm \sqrt{23281}}{2\cdot90}=\dfrac{-41\pm \sqrt{23281}}{180}[/tex]
4x – 9y = 7
–2x + 3y = 4
What number would you multiply the second equation by in order to eliminate the x-terms when adding to the first equation?
Answer:
By 2.
Step-by-step explanation:
You need to eliminated the x-terms, so the first step is to focus only in those terms.
So yo have 4x and -2x, since you are thinking in eliminate then you have this equation>
[tex]4-2*K=0[/tex]
Note that we dont put the x variable, since we are studying its coefficients in the equations system.
Solving for K, Gives us that K=2
So.
Multiplying the second equation by 2 results in
[tex]-4x+6y=8[/tex]
When you put them together, it gives you the following
[tex]4x-9y -4x+6y- 7+8[/tex]
and the final equation is
[tex]-3y=15\\[/tex]
giving you the answer for y, that is [tex]y=-5[/tex]
Answer: 2 and 3.
Step-by-step explanation:
Tabitha is trying to find the equation of a line perpendicular to y= 1/2x - 5 in slope-intercept form that passes through the point (2, -7). which of the following equations will she use.
1. y-(-7) = 1/2(x-2)
2.y-2=1/2(x-(-7))
3.y-(-7)=-2(x-2)
4.y-2=-2(x-(-7))
Answer:
[tex]\large\boxed{3.\ y-(-7)=-2(x-2)}[/tex]
Step-by-step explanation:
The point-slope form of an equation of a line:
[tex]y-y_1=m(x-x_1)[/tex]
m - slope
Let [tex]k:y=m_1x+b_1,\ l:y=m_2x_b_2[/tex].
[tex]l\ \perp\ k\iff m_1m_2=-1\to m_2=-\dfrac{1}{m_1}\\\\l\ \parallel\ k\if m_1=m_2[/tex]
================================================
We have the equation of the line:
[tex]y=\dfrac{1}{2}x-5\to m_1=\dfrac{1}{2}[/tex]
Therefore
[tex]m_2=-\dfrac{1}{\frac{1}{2}}=-2[/tex]
Put it and coorinates of the point (2, -7) to the equation of a line
in the point-slope form:
[tex]y-(-7)=-2(x-2)\\\\y+7=-2(x-2)[/tex]
Let f(x) = 4x - 7 and g(x) = 2x - 3. Find (fog)(4).
Answer:
13
Step-by-step explanation:
(f∘g)(4) is another way of writing f(g(4)).
First, find g(4).
g(x) = 2x − 3
g(4) = 2(4) − 3
g(4) = 5
Now substitute into f(x).
f(x) = 4x − 7
f(g(4)) = 4g(4) − 7
f(g(4)) = 4(5) − 7
f(g(4)) = 13
[tex](f\circ g)(x)=4(2x-3)-7=8x-12-7=8x-19\\\\(f\circ g)(4)=8\cdot4-19=13[/tex]
In circle O, AD and BE are diameters. What is m? 106° 132° 138° 164°
Answer:
It is 132 just took it
Step-by-step explanation:
Each of the pairs of opposite angles made by two intersecting lines is called a vertical angle. The measure of ∠AOE is 132°. The correct option is B.
What are vertical angles?Each of the pairs of opposite angles made by two intersecting lines is called a vertical angle.
In circle O, AD and BE are diameters. Also, the measure of ∠EOD and ∠AOB will be equal because the two angles are vertically opposite angles. Therefore,
∠EOD = ∠AOB = 3x
As it is given that the measure of ∠AOC is 90°. Therefore, we can write,
∠AOC = ∠AOB + ∠BOC
90 = 3x + 0.5x + 34
56 = 3.5x
x = 16
Now, the measure of ∠EOD will be,
∠EOD = 3x
∠EOD = 3(16°)
∠EOD = 48°
Further, we can write,
∠AOD = ∠AOE + ∠EOD
180° = ∠AOE + 48°
∠AOE = 132°
The complete question is mentioned in the below image.
Learn more about Vertical Angles:
https://brainly.com/question/24460838
#SPJ2
If Sn=n^2+3 then t10=?
Answer:
T10= -21
Step-by-step explanation:
If Sn=n^2+3 then t10=?
Sn= n²+5
put n=1, 2
S1= T1 = (1)²+5
=1+5 =6
S2= n²+5
S2=(2)²+5
S2=4+5
S2=9
T2 = S2 - S1
T2 = 9-6
T2=3
T10 = a+(n-1)d
where a = 6, d = -3, n=10
T10= 6+(10-1)*-3
T10=6+(9)*-3
T10=6+(-27)
T10=6-27
T10= -21
Therefore T10= -21 ....
The function f(x)=−5x^2+3 is defined over the domain −4
Answer:
-77 if I understand correctly
Step-by-step explanation:
If the domain is really {-4} and you have the function f(x)=-5x^2+3.
The range is just whatever the result of f(-4) is...
f(-4)=-5(-4)^2+3
f(-4)=-5(16)+3
f(-4)=-80+3
f(-4)=-77
So again if the question is really "The function f(x)=-5x^2+3 is defined over the domain {-4}, what is the range?"... then the answer is just {-77}
7.
chef has 50 pounds of strip Zebra. The trim loss on the strip zebra is
40% and the cooking loss is 60% of the trimmed weight. How many
pounds of trimmed, cooked strip zebra will the chef have left to serve to
his customers?
Answer:
12 pounds
Step-by-step explanation:
After trimming:
50 − 0.40 (50) = 0.60 (50) = 30
After cooking:
30 − 0.60 (30) = 0.40 (30) = 12
Use the graph of f(x) to evaluate the following:
The average rate of change of f from x=0 to x=4 is_____.
Give your answer as an integer or reduced fraction
Answer:
-5/4
Step-by-step explanation:
The average rate of change of f from x=0 to x=4 is_____.
This means we are being asked to evaluate [tex]\frac{f(4)-f(0)}{4-0}[/tex].
To do this we will need to find f(0) and f(4).
f(0) means what y-coordinate corresponds to x=0 on the curve. Find x=0, the curve is above there, go straight up and see y=5 there. This means f(0)=5.
f(4) means what y-coordinate corresponds to x=4 on the curve. Find x=4, then curve is above there, go straight up and see y=0 there. This means f(4)=0.
So we have:
[tex]\frac{f(4)-f(0)}{4-0}=\frac{0-5}{4-0}=\frac{-5}{4}[/tex].
Which expression is equivalent to log3(x + 4)?
log3 - log(x + 4)
log12 + logx
log3 + log(x + 4)
log 3/log(x+4)
Answer:
log[3(x+4)] is equal to log(3) + log(x + 4), which corresponds to choice number three.
Step-by-step explanation:
By the logarithm product rule, for two nonzero numbers [tex]a[/tex] and [tex]b[/tex],
[tex]\log{(a \cdot b)} = \log{(a)} + \log{(b)}[/tex].
Keep in mind that a logarithm can be split into two only if the logarithm contains the product or quotient of two numbers.
For example, [tex]3(x + 4)[/tex] is the number in the logarithm [tex]\log{[3(x + 4)]}[/tex]. Since [tex]3(x + 4)[/tex] is a product of the two numbers [tex]3[/tex] and [tex](x + 4)[/tex], the logarithm [tex]\log{[3(x + 4)]}[/tex] can be split into two. By the logarithm product rule,
[tex]\log{[3(x + 4)]} = \log{(3)} + \log{(x + 4)}[/tex].
However, [tex]\log{(x + 4)}[/tex] cannot be split into two since the number inside of it is a sum rather than a product. Hence choice number three is the answer to this question.
Answer:
c
Step-by-step explanation: